Analysis of children and youth social problems within the European Union - Adele Della Pieta (International Seminar on Social Work Update, 2023)
The objective of the research is to analyse the social problems encountered by minors within the European Union. The first chapter focuses on the role of the social work within the child protection system; the study is carried out by comparing the child protection system in Italy and Latvia. The second part of the research takes the European Union as a case study, initially analysing the rights and advantages that a young European citizen has. Secondly, the most relevant social problems for young Europeans are analysed, such as lack of employment, drug use and addiction and the possibility of being bullied and cyber-bullied. The research was conducted by analysing secondary data (scientific articles, EU reports, EUROSTAT statistics, journal of youth studies). The results highlighted by the research were reported in the first part of the study, within the comparison between Italy and Latvia, where a difference in the development of a protection system for minors is found. On the contrary, the analysis at the European level, where social issues are shared by young European citizens, is balanced. In conclusion, it is possible to point out that both at the national level and at the international level of the EU there are child protection systems and laws that specifically deal with the social problems of young people; nevertheless, it is relevant to emphasise that each State has a different situation. Keywords: Child protection, social problems, children, youth, the European Union